The course of metastatic prostate cancer under treatment - (:unkn) unknown (SPRINGER INTERNATIONAL PUBLISHING AG, 2014)
The first-line management of metastatic prostate cancer is hormonal therapy. However, resistance to this treatment will emerge within an average of 24 months. Our purpose was to determine the course of metastatic prostate cancer under treatment. A total of 56 patients who were diagnosed with metastatic prostate cancer were enrolled. As initial management, 3 kinds of hormonal therapy consisting of bilateral orchiectomy (BSO) alone, BSO + anti-androgene (AA) and LH-RH + AA were applied. The patients were followed until the emergence of hormone resistance. Serum PSA levels at the time of first diagnosis, post-treatment nadir PSA levels, time to nadir PSA, time to hormonal resistance and PSA levels at hormonal resistance were assessed, retrospectively. The localization and number of metastases and the survival term from the beginning of the emergence of hormone resistance until death were investigated No significant differences could be established between the groups. The mean time to reach hormone refractory status was 30.3 months for the whole study group. The average term of survival was 42.7 months for the whole group. Distance metastases were found in 8 patients during follow-up. There were no statistical differences between the groups in terms of treatment modalities applied for metastatic prostate cancer. Patients with androgen independent prostate cancer demonstrated progression despite chemical or surgical castration, and had poor prognosis. Initial hormonal therapy failed after an average of 2 years in metastatic prostate cancer.
Keywords: Metastatic prostate cancer; Treatment modality; Course; ANDROGEN-DEPRIVATION THERAPY; CARDIOVASCULAR COMPLICATIONS; HORMONAL-THERAPY; CASTRATION; BLOCKADE; TRIAL; MEN; BICALUTAMIDE; ORCHIECTOMY; MANAGEMENT